2010
DOI: 10.1007/s11307-010-0447-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 11C-Methionine PET and 18F-FDG PET in Patients with Primary Central Nervous System Lymphoma

Abstract: There was no significant difference between T/N ratios using MET PET and FDG PET, although uptake of MET in CNS lymphoma was significantly lower than that of FDG. MET PET showed as high a sensitivity as FDG PET for the detection of primary lesions in patients with CNS lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…It is well known that FDG-uptake on diffuse large B-cell lymphoma is higher than that on other types of lymphoma, and this characteristic feature could be helpful in differentiating between B-cell lymphoma and other histological tumors [26]. Similarly, PET can identify degenerative diseases, multiple sclerosis, infectious diseases and cerebral infarction [27]. In recent years, the use of 18 F-FDG PET and PET/CT has increased in routine practice at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that FDG-uptake on diffuse large B-cell lymphoma is higher than that on other types of lymphoma, and this characteristic feature could be helpful in differentiating between B-cell lymphoma and other histological tumors [26]. Similarly, PET can identify degenerative diseases, multiple sclerosis, infectious diseases and cerebral infarction [27]. In recent years, the use of 18 F-FDG PET and PET/CT has increased in routine practice at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid metabolic imaging with MET-PET possesses high specificity in tumor detection, tumor delineation and differentiation of benign from malignant lesions in the brain [11]. MET-PET examination in PCNSL is limited and only a few reports demonstrate its diagnostic usefulness and evaluate the therapeutic effect [4, 12]. In our previous reports, PCNSL with typical MR findings showed, without exception, increased FDG and MET uptakes in the tumor before treatment [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nuutinen et al [111] studied 32 lymphoma patients and found MET-PET highly sensitive for the detection of disease sites although there was no correlation between MET uptake and patient outcome. Also, MET-PET has an advantage over FDG-PET in imaging of CNS lymphoma [112]. While these results are encouraging, it should be noted that no studies have shown the usefulness or cost-effectiveness of amino acid or nucleoside tracers in large patient cohorts.…”
Section: Newer Pet Tracersmentioning
confidence: 99%